عہد جاہلی میں ثقفی اعیان کا مقام و کردار: THE STATUS AND ROLE OF THAQAFI NOBLES IN THE PRE-ISLAMIC ERA - Sahib Din; Humayun Abbas, (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
The pre-Islamic era, often referred to as the Jahiliyyah period, was marked by tribal affiliations, leadership, and social hierarchy. Among the prominent tribes of the Arabian Peninsula, the Thaqif tribe held a distinguished position, particularly in the city of Taif. This study explores the status and role of the Thaqafi nobles during this period, shedding light on their contributions to tribal politics, warfare, trade, and social dynamics. The Thaqafi leaders were renowned for their wisdom, courage, and ability to resolve disputes, which solidified their influence both within their tribe and beyond.This research delves into the socio-political landscape of the time, examining how the Thaqafi nobles-maintained power, fostered alliances, and played a crucial role in preserving the cultural and economic significance of Taif. It also highlights their contributions to poetry, diplomacy, and leadership, which earned them a place of respect in the annals of Arabian history. By analyzing historical accounts and narratives, this paper aims to provide a comprehensive understanding of the Thaqafi tribe's role in shaping pre-Islamic Arab society.The study underscores how the traits of resilience, honor, and strategic acumen demonstrated by the Thaqafi nobles contributed to their lasting legacy, bridging the gap between the tribal values of Jahiliyyah and the advent of Islam.